Legal Certainty, Justice, and Maqasid al-Shari'ah in Polygamy Permits: A Case Study of Kediri Religious Court - Muhammad Solikhudin; Abdelmalek OUICH; Shofwan Al-Jauhari; Ashima Faidati (Indonesian Journal of Islamic Law, 2024)
Polygamy has been a problem with pros and cons until now. This also includes permission for polygamy carried out by the husband for reason of high sexual desire or hypersexuality, which causes the husband to take permission for polygamy to the Religious Court. This is what happened in the Kediri Regency Religious Court Number 3826/Pdt.G/2023/PA.Kab.Kdr. This article is library research, qualitative in nature, and uses a conceptual and statutory approach. The results of this research show that the practice of polygamy permit is in accordance with aspects of legal justice, legal certainty and legal benefit. As for maqasid al-shari'ah, if it is related to the case of polygamy permit, it can be understood that, First, legal texts and rules are not separate from their purpose. In Islam, there is a rule that polygamy is limited to four wives, the purpose of which is to worship Allah and form a harmonious family and must fulfill the positive legal aspects, namely permission from the first wife. Second, combine universal principles with arguments used for specific cases. In this case, even though there is a text about polygamy, it still requires permission from the first wife, and is connected to the principle of hifz al-usrah which contains hifz al-din, hifz al-al-'aql, hifz al-nasl, and hifz al-mal. All these principles emphasize the teachings of Islam rahmatan lil 'alamin. Third, achieving benefits and preventing harm. Therefore, polygamy must be accompanied by permission from the first wife to realize the benefits and the building of the family must prioritize the benefits aspect and avoid harm. Fourth, consider the final result. In this case, the implication of the husband's actions, if the impact is that the family structure is not harmonious, it is better for the husband to marry only one wife. So that the goals of marriage can be achieved. This is in accordance with the purposefulness feature conveyed by Jasser Auda.